Consumer preferences for apple : comparing the results of contingent valuation method and a real purchasing situation - Botelho, Anabela (2013)
Increased competition in agro-food systems has motivated the appearance of new or more heterogeneous products. In addition consumers are increasingly more demanding about product information and characteristics, associated with a move towards products that differentiate themselves by its environmental characteristics, health effects, quality, origin, etc. Thus consumers’ preferences became more complex and diversified. Consumers are faced with a great variety of competing products and firms are ever more interested in identifying the attributes, or the combination of attributes, that are most valued by consumers. Valuation studies have sought to determine the influence of certain attributes in the willingness to pay (WTP) measures, including the importance of organically produced fruit and vegetables (Zhao et al., 2007; Radman, 2005) or the effect of providing additional information, with respect for example the health benefits, (Ginon et al. 2007; Marette et al., 2010; Bocaletti and Nardella, 2000). Considering a set of relevant characteristics, this paper investigates the influence of the attribute “National Variety” on rank order preferences and on the willingness to pay measures. The procedure assesses the effect of the origin of apple variety, comparing the values from an open ended question on the willingness to pay for two apple varieties. The elicitation of the value is performed with information on this characteristic and after tasting and rating the varieties. These results are then compared to the value elicited in a real purchasing situation, where the respondent can buy the preferred apple (one kg) if the elicited value on the open ended question is superior to an extracted random price. In sum, the paper demonstrates the applicability of the Contingent Valuation Method to eliciting the effect of information on an attribute on elicited WTP; It tests for hypothetical bias in this elicitation framework. The results show that predicted mean WTP for national varieties is lower than the predicted willingness to pay for foreign varieties. In addition, the results reveal a statistically significant hypothetical bias in the case of the National varieties, but not in the case of the foreign varieties.